The language electroacoustic music - Emmerson, Simon (London Macmillan Publishers, 1986)
Since the inception of electroacoustic music in 1948, much has been written about technical developments. This book is one of the first to examine aesthetic issues central to this rapidly developing genre. It brings together composers from leading academic departments and studios in Britain, the United States, Canada and Paris with a wide range of approaches and opinions, resulting in a study which is likely to have a marked impact on current debates on the future of electroacoustic music.The book is divided into three sections. The first, Culture and Language, considers the relationship between music and the listener's perception and expectation. Materials and Lanugage looks at the types of materials available to composers and the way in which the internal structure of the sound can have implications for the overall structure of a piece. The final section, The Influence of New Technology, considers the relationship between computer systems and the music they are helping to create.